Review: Systematic review of the utility of the fetal cerebroplacental ratio measured at term for the prediction of adverse perinatal outcome. (June 2017) - Dunn, Liam; Sherrell, Helen; Kumar, Sailesh
Abstract: Aim: This systematic review evaluates the utility of the fetal cerebroplacental ratio (CPR) when assessed at term (from 37 + 0 weeks gestation) as a predictor of adverse obstetric and perinatal outcomes. Data sources and search strategy: An electronic search of Pubmed and Embase using variations of 'cerebroplacental ratio' and 'cerebroumbilical ratio' was conducted by two independent reviewers. Full text studies written in English that reported on low CPR and its correlation with relevant obstetric and perinatal outcomes were included. Results: Twenty one studies satisfied inclusion with 13 prospective and eight retrospective analyses. Fetal CPR was predictive of caesarean section for intrapartum fetal compromise, small for gestational age and fetal growth restriction and neonatal intensive care unit admission. Low CPR was also significantly associated with abnormal fetal heart rate pattern, meconium stained liquor, low Apgar score, acidosis at birth and composite adverse perinatal outcome scores. The CPR when taken at term had comparable if not better predictive value than that when taken at preterm. Most studies included small for gestational age fetuses and postdate pregnancies. Subtle variation existed in the threshold for low CPR. Conclusion: The CPR at term has a strong association with adverse obstetric and perinatal outcomes. This review suggests the predictive utility of CPR at term is promising however there is insufficient evidence to demonstrate its value as a stand-alone test. Inclusion of CPR as a component of clinical care may help better identify fetuses at risk of adverse outcome, and this should be tested with randomised control trials. Highlights: The cerebroplacental ratio (CPR) assesses both fetal and placental circulation. Low CPR at term is associated with adverse obstetric and perinatal outcomes. Predictive utility is inadequate as a stand-alone antenatal screening tool at term.